Tuning Hole Transport Properties via Pyrrole Derivation for High‐Performance Perovskite Solar Cells. (1st March 2023) - Zhou, Junjie; Li, Hang; Tan, Liguo; Liu, Yue; Yang, Junliang; Hua, Ruimao; Yi, Chenyi
Abstract: Hole transport materials (HTMs) with high hole mobility, good band alignment and ease of fabrication are highly desirable for perovskite solar cells (PSCs). Here, we designed and synthesized novel organic HTMs, named T3, which can be synthesized in high yields with commercially available materials, featuring a substituted pyrrole core and triphenylamine peripheral arms. The capability of functionalization in the final synthetic step provides an efficient way to obtain a variety of T3‐based HTMs with tunable energy levels and other properties. Among them, fluorine‐substituted T3 (T3‐F) exhibits the best band alignment and hole extraction properties, leading to PSCs with outstanding PCEs of 24.85 % and 24.03 % (certified 23.46 %) for aperture areas of 0.1 and 1 cm 2, respectively. The simple structure and tunable performance of T3 can inspire further optimization for efficient PSCs. Abstract : Low‐cost hole transport materials T3, featuring a substituted pyrrole core and triphenylamine peripheral arms, have been designed and synthesized for high performance perovskite solar cells. The capability of functionalization in the final synthetic step provides an efficient way to tune energy levels and other properties of T3 materials.